Utilization of in Vitro Anther Culture in Spelt Wheat Breeding - Lantos, Csaba (Plants (Basel), 2019)
The efficiency of in vitro anther culture was screened in a full diallel population of four spelt wheat genotypes and ten F(1) hybrids. Genotype dependency was observed based on the data of embryo-like structures (ELS), green-, albino plantlets. In the diallel population and ten F(1) hybrids, the green plantlets production ranged from 13.75 to 85.00 and from 6.30 to 51.00, respectively. The anther culture-derived plants of F(1) hybrids were grown up in the nursery. At the harvest, 436 spontaneous doubled haploid (DH) plants were identified among the 1535 anther culture-derived transplanted and grown up individual plants. The mean of spontaneous rediploidization was 28.4% which ranged from 9.76% to 54.24%. In two consecutive years, the agronomic values of ‘Tonkoly.pop1’ advanced line were compared with seven DH lines of ‘Tonkoly.pop1’ in the nursery. The DH lines achieved competitive values in comparison with ‘Tonkoly.pop1’ advanced line based on the 11 measured parameters (heading date, plant height, yield, hardness, width and length of seed, TKW, hulling yield, flour yield, protein and wet gluten content). These observations presage the efficient utilization of anther culture in spelt wheat breeding.